KOMUNIKASI KELUARGA ANTARA ORANG TUA DALAM MENDAMPINGI PROSES BELAJAR HYBRID PADA MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS GUNADARMA - Rina Astriani; Rani Puspita (Jurnal Sosial Humaniora dan Pendidikan, 2024)
The purpose of this study was to find out how family communication between parents and students in accompanying the hybrid learning process in Gunadarma University students. The method used in this study was that researchers use qualitative descriptive methods. Data collection techniques that researchers do in the form of online virtual interviews and observations of sources and informants. This research uses the theory of Cognitivism by Jean Piaget. Based on the results of observations and interviews, researchers concluded that family communication has been successfully carried out in the form of a close relationship and mutual communication between parents and children in trust, motivating children in learning, and parental assistance will increase interest in learning in children to stay focused on learning goals.